A preparation method of a lead-tin-titanium-tellurium-gallium alloy solder strip, a product and application
Patent Information
- Application Number
- CN202611452042.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本发明的目的在于提供一种铅锡钛碲镓合金焊料条的制备方法及产品和应用,以解决上述背景技术中提出的现阶段焊料合金制备的焊料工艺面临窗口窄、成分控制难、杂质引入及批次一致性差等工业化生产难题
1.本发明通过“分步制备+梯度温控”的工艺设计,实现了钛的高效合金化(S1、真空高温熔炼);碲的低温稳定引入(S2、600~750℃制备母合金);各元素的均匀分散(S3、保护层覆盖+充分搅拌+梯度降温)。该工艺路线使合金成分的精准控制和产品批次的一致性成为可能,解决了现有技术中“成分控制难、杂质引入及批次一致性差”的工业化生产难题,为铅锡钛碲镓合金焊料条的规模化、稳定化工业生产奠定了工艺基础。
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of lead-acid battery processing, specifically relating to a method for preparing a lead-tin-titanium-tellurium-gallium alloy solder bar, the product thereof, and its application in internal welding of batteries. Background Technology
[0002] Lead-acid batteries, as a mature, safe, and economical secondary chemical power source, are widely used in electric engineering machinery (such as electric scissor lifts, electric boom lifts, and electric forklifts). However, with the rapid development of electric engineering machinery, the phenomenon of battery terminal and busbar root fractures is increasing. Studies have shown that batteries experience high-frequency, high-amplitude vibrations during transportation and operation. Under high-frequency and repeated vibrations, the electrode group slides up and down along the bottom of the battery, at which point the roots of the terminals and busbars become stress points. Failure analysis indicates that fractures mainly occur at the junction of the terminals and busbars, and the cause of failure is low-cycle fatigue resulting from plastic deformation of the lead alloy under external force, leading to fracture.
[0003] Because the terminals and bridges inside the battery are made of relatively soft lead or lead alloys, long-term exposure to high-frequency vibrations will cause capillary cracks to form at the stress points, exposing metallic lead. The positive plate is connected to the positive terminal and the positive bridge. The main component of the active material of the positive plate is lead dioxide. In a dilute sulfuric acid atmosphere, an electrochemical reaction occurs at the capillary cracks to form lead sulfate. The electrochemical reaction is: Pb + PbO2 + 2H2SO4 = 2PbSO4 + 2H2O. The volume of lead sulfate is approximately 2.7 times that of metallic lead, causing the cracks to be further torn apart, continuing to expose lead. The reaction continues until the cracks are completely corroded and broken, ultimately leading to battery failure.
[0004] Most current solders are tin-based, compounded with copper, nickel, and germanium, and can also selectively add elements such as gallium and tellurium. The synergistic effect of these multiple elements improves the mechanical strength and corrosion resistance of the solder to some extent. However, this approach has significant drawbacks: First, the tin base results in a large amount of tin used, leading to high costs for alloy raw materials. Second, it belongs to a lead-free solder system, while lead-acid battery tabs often use lead-calcium alloys, lead-calcium-tin-aluminum alloys, lead-calcium-rare earth alloys, and lead-antimony alloys, and the terminals often use lead-tin alloys and lead-antimony alloys. Lead-free solders have poor compatibility with lead-based base materials, making it difficult to guarantee the quality of welded joints for tabs, terminals, and bridges, and making it unsuitable for the series-parallel welding conditions inside lead-acid batteries.
[0005] Existing technologies have addressed the shortcomings of relying on the synergistic effects of multiple elements, such as patent document CN116275684A – a solder alloy and its preparation method and application. This approach attempts to optimize soldering performance through a multi-element alloy composition of lead, titanium, tellurium, gallium, and tin. However, this method suffers from numerous industrial production challenges, including unreasonable titanium addition parameters, the easy volatilization of the functional element tellurium during high-temperature preparation, and the introduction of impurities through the reaction of titanium with the protective gas. These issues directly result in difficulty in precisely controlling the solder alloy composition, poor batch-to-batch performance consistency, and an inability to achieve large-scale, stable industrial production applications. Therefore, a new technical solution is needed to address these problems. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing lead-tin-titanium-tellurium-gallium alloy solder bars, as well as products and applications, to solve the industrial production problems faced by the current solder alloy preparation process, such as narrow window, difficulty in composition control, introduction of impurities, and poor batch consistency, as mentioned in the background art.
[0007] To achieve the above objectives, the present invention provides the following three technical solutions: Firstly, this invention provides a method for preparing lead-tin-titanium-tellurium-gallium alloy solder bars, comprising the following specific steps: The lead-tin-titanium-tellurium-gallium alloy solder bar is smelted from the following components by weight percentage: titanium 0.005-0.1%, tellurium 0.05-0.2%, gallium 0.01-0.15%, tin 1.0-2.0%, with the balance being lead and unavoidable impurities; S1. The sponge titanium and the first part of tin are loaded into the furnace in a titanium-tin-titanium sandwich manner, and heated and melted under vacuum conditions of less than 1.0 Pa and temperature of 1350-1550℃. After melting and holding at the temperature for 35-55 minutes, the mixture is cast, vacuum cooled and crushed to obtain titanium-tin intermediate alloy particles. The weight ratio of sponge titanium to the first part of tin is 1:5-10. S2. Place the second part of tin, gallium, and tellurium in a vacuum quartz ampoule or a high-purity graphite crucible, and heat it to 600-750°C for 2-4 hours under a protective atmosphere to melt it. Then cool and crush it to obtain tin-gallium-tellurium master alloy particles. The second part of tin is the remaining tin after subtracting the first part of tin from the total weight of tin in the lead-tin-titanium-tellurium-gallium alloy. The protective atmosphere is a vacuum or an inert atmosphere. S3. After heating and melting the lead ingot, raise the temperature to 600-700℃, and sequentially add the titanium-tin intermediate alloy particles prepared in S1 and the tin-gallium-tellurium master alloy particles prepared in S2. Cover the surface of the smelting system with a protective layer, stir until completely melted and evenly mixed, and cool to 400-450℃ to obtain a lead-tin-titanium-tellurium-gallium alloy liquid. The protective layer is borax or charcoal powder. After the alloy particles are completely melted, continue stirring for 20-60 minutes. S4. Inject the lead-tin-titanium-tellurium-gallium alloy liquid obtained in S3 into the pre-made solder forming mold, cool to room temperature, demold, and obtain lead-tin-titanium-tellurium-gallium alloy solder bar. The first portion of tin and the second portion of tin together constitute the total amount of tin in the lead-tin-titanium-tellurium-gallium alloy.
[0008] Second aspect: The present invention provides a lead-tin-titanium-tellurium-gallium alloy solder bar, which is prepared by the method described in the first aspect.
[0009] Third aspect: The present invention provides a lead-tin-titanium-tellurium-gallium alloy solder bar prepared by the method described in the first aspect for use in the internal welding of a storage battery, wherein the solder bar is used for series and parallel welding of the tabs, terminals and bridge structures of the storage battery plates.
[0010] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention achieves efficient titanium alloying (S1, vacuum high-temperature melting); low-temperature stable introduction of tellurium (S2, preparation of master alloy at 600-750℃); and uniform dispersion of various elements (S3, protective layer coverage + thorough stirring + gradient cooling) through a "stepwise preparation + gradient temperature control" process design. This process route enables precise control of alloy composition and batch consistency of products, solving the industrial production problems of "difficulty in composition control, impurity introduction, and poor batch consistency" in existing technologies. It lays the technological foundation for the large-scale and stable industrial production of lead-tin-titanium-tellurium-gallium alloy solder bars.
[0011] 2. This invention employs a unique three-step preparation process, solving the problems of high melting point of titanium (Ti) and easy volatility of tellurium (Te), ensuring precise control of alloy composition and batch stability, and realizing large-scale and stable industrial production. Specifically: Titanium alloying: By pre-preparing a titanium-tin master alloy, high-melting-point sponge titanium is smelted with a portion of tin at 1350–1550℃. This method not only reduces the difficulty of titanium alloying but also avoids the lumps that easily occur when directly adding elemental metals, making the subsequent smelting process more stable. Tellurium alloying: The tellurium alloying process is separated, and a tin-gallium-tellurium master alloy is prepared at a low temperature of 600–750℃. This temperature is far below the boiling point of tellurium (989℃), effectively suppressing the violent volatilization of tellurium at high temperatures from the source.
[0012] 3. This invention utilizes a titanium-tin-titanium sandwich furnace loading system, allowing tin to envelop titanium from both sides during melting, gradually introducing titanium into the melt. This avoids titanium spalling and segregation issues, ensuring the compositional uniformity of the titanium-tin master alloy. Furthermore, vacuum melting is employed to minimize the removal of reactive gases in the atmosphere, fundamentally preventing the risk of impurities introduced by the reaction between titanium and the protective gas. This guarantees the high purity of the titanium-tin master alloy, thereby ensuring the final solder alloy product quality.
[0013] 4. This invention significantly reduces the alloying temperature of tellurium to 600–750°C, allowing tin and tellurium, and gallium and tellurium, to fully react at this temperature to form intermetallic compounds such as SnTe and Ga2Te3. This temperature is far below the boiling point of tellurium, solving the tellurium volatilization problem at the source of the process. Simultaneously, preparing master alloy particles before adding them in subsequent steps ensures that tellurium is uniformly introduced into the alloy system in compound form, avoiding compositional segregation caused by large density differences when directly adding elemental tellurium. Furthermore, covering the surface of the smelting system with a protective layer: on the one hand, isolates the contact between air and the alloy liquid surface, preventing the oxidation of elements such as lead and tin at high temperatures; on the other hand, it inhibits further volatilization of residual tellurium, further ensuring the accuracy of the alloy composition.
[0014] 5. The solder bar of this invention uses lead as the base material and has a tin content of only 1.0-2.0%. It exhibits good welding compatibility with lead-based base materials such as lead-calcium alloy, lead-calcium-tin-aluminum alloy, lead-calcium-rare earth alloy, or lead-antimony alloy for lead-acid batteries and terminals (usually lead-tin alloy or lead-antimony alloy), achieving excellent metallurgical bonding and ensuring the quality of the welding joints of the tabs, terminals, and bridges. Simultaneously, the low tin content significantly reduces raw material costs compared to tin-based solders. Furthermore, titanium, even at extremely low content (0.005-0.1%), can form fine intermetallic compounds that disperse throughout the alloy matrix, playing a role in precipitation strengthening and grain refinement, thereby improving the alloy's strength and corrosion resistance. Gallium can rapidly form a dense passivation layer on the alloy surface, inhibiting further oxidation or corrosion. Tellurium, in synergy with titanium and tin, refines the grain structure, increases strength, and improves corrosion resistance. Titanium, tellurium, gallium, tin and lead are combined in specific proportions to significantly improve the mechanical strength and corrosion resistance of the alloy even with extremely low titanium content. A dense passivation layer is rapidly formed on the alloy surface, so even if capillary cracks are formed at the pole and bridge root due to vibration, severe electrochemical corrosion is not likely to occur. Detailed Implementation
[0015] The following examples are used to further illustrate the content of the present invention and do not limit the application of the present invention (all percentages below are weight percentages).
[0016] The raw materials used in the following examples are: titanium (sponge titanium, purity ≥99.5%), tin (tin ingot, purity ≥99.9%), tellurium (purity ≥99.9%), gallium (purity ≥99.99%), and lead (electrolytic lead, purity ≥99.99%), all of which are commercially available industrial-grade raw materials. Example 1:
[0017] The lead-tin-titanium-tellurium-gallium alloy solder bar provided in this embodiment The solder alloy formula is: 0.05% titanium, 0.15% tellurium, 0.10% gallium, 1.6% tin, and the balance is lead (i.e., 98.10% lead).
[0018] The specific steps of its preparation method are as follows: Step 1: Preparation of titanium-tin master alloy: Weigh out sponge titanium and tin blocks according to a Ti:Sn = 1:8 weight ratio. Dry the sponge titanium at 85℃ and clean the tin blocks with alcohol. Place the titanium-tin-titanium interlayer in a vacuum arc furnace and heat it to 1450℃ under vacuum conditions (vacuum degree less than 1.0Pa). Hold the temperature for 45 minutes. After melting, cast the mixture. After vacuum cooling for 30 minutes, remove it from the furnace and demold it to prepare a titanium-tin intermediate alloy block. Crush the block into granules for later use.
[0019] Step 2: Preparation of tin-gallium-tellurium master alloy: The remaining tin after deducting the amount of tin consumed in step one, along with the amount of gallium and tellurium in the formula, are placed in a high-purity graphite crucible. After evacuation, the crucible is filled with argon gas for protection, heated to 680°C, and held for 3 hours to ensure full alloying. After cooling, the crucible is broken into particles to prepare tin-gallium-tellurium master alloy particles.
[0020] Step 3: Dilute into molten lead: The required amount of lead ingots is added to the alloy furnace and heated to melt. The temperature is then raised to 650°C, and stirring is started. The titanium-tin intermediate alloy particles prepared in step one and the tin-gallium-tellurium master alloy particles prepared in step two are added sequentially. A charcoal powder protective layer is placed on the surface of the molten pool. Stirring continues until the master alloy particles are completely melted, and then stirring is continued for another 40 minutes to ensure uniform mixing. The temperature is lowered to 420°C, and the alloy liquid is poured into a pre-made solder forming mold. After cooling to room temperature, the mold is removed to prepare lead-tin-titanium-tellurium-gallium alloy solder bars. Example 2:
[0021] The lead-tin-titanium-tellurium-gallium alloy solder bar provided in this embodiment The solder alloy formula is: 0.005% titanium, 0.18% tellurium, 0.15% gallium, 2.0% tin, and the balance is lead (i.e., 97.665% lead).
[0022] The preparation method is the same as in Example 1, only the formulation amounts are different. Furthermore, the Ti:Sn ratio in the titanium-tin master alloy is 1:10. Example 3:
[0023] The lead-tin-titanium-tellurium-gallium alloy solder bar provided in this embodiment The solder alloy formula is: 0.1% titanium, 0.12% tellurium, 0.01% gallium, 1.0% tin, and the balance is lead (i.e., 98.77% lead).
[0024] The preparation method is the same as in Example 1, only the formulation amounts are different. Furthermore, the Ti:Sn ratio in the titanium-tin master alloy is 1:5. Example 4:
[0025] The lead-tin-titanium-tellurium-gallium alloy solder bar provided in this embodiment The solder alloy formula is: 0.03% titanium, 0.2% tellurium, 0.01% gallium, 1.0% tin, and the balance is lead (i.e., 98.76% lead).
[0026] The preparation method is the same as in Example 1, only the formulation amount is different. Example 5:
[0027] The lead-tin-titanium-tellurium-gallium alloy solder bar provided in this embodiment The solder alloy formula is: 0.08% titanium, 0.05% tellurium, 0.08% gallium, 1.6% tin, and the balance is lead (i.e., 98.19% lead).
[0028] The preparation method is the same as in Example 1, only the formulation amount is different.
[0029] In this invention, inductively coupled plasma optical emission spectrometry (ICP-OES) was used to perform ICP composition analysis on the solder alloys prepared in Examples 1-5. The results are shown in the table below: ; As shown in the table above, the content of each component in the solder alloy prepared by the present invention is basically consistent with the design value of the formula. In particular, the yield of tellurium is high (all above 98%). Therefore, by controlling the alloying temperature of tellurium in the low temperature range of 600 to 750°C, the present invention effectively suppresses the volatilization of tellurium and ensures the accuracy of the alloy composition.
[0030] Comparative Example 1: The solder bar provided in this comparative example The solder alloy formula is: 0.15% tellurium, 0.10% gallium, 1.6% tin, with the balance being lead (i.e., 98.15% lead), and no titanium is added.
[0031] The specific steps of its preparation method are as follows: Step 1: Preparation of tin-gallium-tellurium master alloy: The gallium and tellurium in the formula and a portion of tin (the amount of tin used is the same as the amount of tin consumed in step one of Example 1) are placed in a high-purity graphite crucible, vacuumed, and then filled with argon for protection. The crucible is heated to 680°C, held for 3 hours, cooled, and then crushed into particles to prepare tin-gallium-tellurium master alloy particles.
[0032] Step 2: Dilute into molten lead: Add the required amount of lead ingots to the alloy furnace and heat to melt. Continue heating to 650°C, start stirring, add the remaining tin in the formula and the tin-gallium-tellurium master alloy particles prepared in step one, cover the surface of the molten pool with a protective layer of charcoal powder, continue stirring until completely melted, and then continue stirring for 40 minutes to mix evenly. Cool down to 420°C, pour the alloy liquid into the solder mold to prepare solder bars.
[0033] Comparative Example 2: The solder bar provided in this comparative example The solder alloy formulation is as follows: 0.05% titanium, 0.15% tellurium, 0.10% gallium, 1.6% tin, with the balance being lead (i.e., 98.10% lead), which is the same as the formulation in Example 1.
[0034] The specific steps of its preparation method (using the existing one-step high-temperature process) are as follows: Add the required amount of lead ingots to the alloy furnace and heat to melt. Continue heating to 1350℃, then add sponge titanium, tin ingots, tellurium and gallium in sequence. Cover the surface of the molten pool with a protective layer of charcoal powder. Stir until completely melted, then continue stirring for 80 minutes to ensure uniform mixing. Cool down to 420℃ and inject the alloy liquid into a solder mold to prepare solder bars.
[0035] Comparative Example 3: This comparative example uses commercial lead-tin solder, Sn 5wt%, balance lead; finished solder bars were purchased directly from external suppliers.
[0036] Comparative Example 4: This comparative example uses commercial lead-antimony solder, with Sb 3wt%, Sn 1wt%, and the balance being lead; finished solder bars were purchased directly from external suppliers.
[0037] First, the solder alloys prepared in Examples 1 to 5 above were compared with those in Comparative Examples 1 to 4 in terms of electrochemical corrosion resistance.
[0038] Test Method: The material to be tested was fabricated into a test electrode (a) with dimensions (length × width × thickness) of 100mm × 50mm × 2mm. Electrolytic lead was fabricated into an auxiliary electrode (b) with dimensions (length × width × thickness) of 100mm × 50mm × 2mm. A dilute sulfuric acid electrolyte (c) with a density of 1.35 g / ml was added to the electrolytic cell. Electrode a was immersed in electrolyte c as the anode and connected to the positive terminal of the power supply. Auxiliary electrode b was immersed in electrolyte c as the cathode and connected to the negative terminal of the power supply. The power supply output a 3A current, and the electrochemical corrosion test was continuously performed for 240 hours. After the test, the corrosion layer on the surface of electrode a was cleaned with a sugar-alkali solution, and the electrode was weighed. The percentage of weight loss before and after the test was calculated. The test results are shown in the table below. ; It can be seen from the above table: (1) The weight loss rate (0.48% to 0.72%) of the solder alloys prepared in Examples 1 to 5 of the present invention is much lower than that of the commonly used alloys in Comparative Example 3 (6.7%) and Comparative Example 4 (8.6%), indicating that the solder alloys of the present invention have significantly better electrochemical corrosion resistance.
[0039] (2) The weight loss rate of Comparative Example 1 (without titanium) was 2.35%, which was significantly higher than that of the other examples, proving that even within the low titanium content range (0.005-0.1%) of the present invention, the addition of titanium still plays an irreplaceable role in improving corrosion resistance.
[0040] (3) The weight loss rate of Comparative Example 2 (using the existing one-step high-temperature process) was 1.52%, which was higher than that of the other examples. This is because the tellurium volatilized at high temperature, resulting in the actual tellurium content being lower than the design value, and the corrosion resistance of the alloy was not fully utilized.
[0041] The solder alloys prepared in Examples 1-5, Comparative Examples 1-2, and commercially available lead-tin solder alloys (Comparative Examples 3 and 4) were then used to make batteries (single-factor comparison, only the solder alloys were replaced) for vibration resistance comparison tests.
[0042] The test method is as follows: The battery is fixed on a vibration table and subjected to a continuous vibration test for 48 hours at an amplitude of 5mm, a maximum acceleration of 50m / s², and a frequency of 30Hz±2Hz. The battery open-circuit voltage is monitored every 12 hours. After the test, the battery is tested to see if it can be charged and discharged normally. The test results of the open-circuit voltage of the vibration test are shown in the table below: ; It can be seen from the above table: (1) The batteries using common alloys as solder in Comparative Examples 3 and 4 showed an abnormal voltage drop during the vibration resistance test. After 48 hours, the voltage dropped to 0V and could not be charged and discharged normally.
[0043] (2) The battery using Comparative Example 1 (without titanium) solder could still charge and discharge normally after 48 hours, but the voltage drop (from 6.61V to 6.50V) was significantly greater than that of the other examples (from 6.61 to 6.62V to 6.58 to 6.59V), indicating that the addition of titanium plays an important role in maintaining the voltage stability of the battery under vibration.
[0044] (3) The battery using the solder of Comparative Example 2 (one-step high-temperature process) also showed a greater voltage drop than the other examples, further demonstrating the advantages of the step-by-step preparation process of the present invention.
[0045] (4) The batteries using the solder alloys of Examples 1 to 5 of the present invention showed virtually no decrease in open-circuit voltage (remaining at 6.58 to 6.59V) after undergoing a 48-hour rigorous vibration test, and could still charge and discharge normally. This indicates that the solder alloys of the present invention have significantly better vibration resistance.
[0046] In summary, this invention, through optimizing the alloy formula and combining it with a scientifically sound stepwise preparation process (first preparing a titanium-tin master alloy, then preparing a tin-gallium-tellurium master alloy, and finally diluting it into molten lead), successfully prepared a solder alloy with both excellent corrosion resistance and vibration resistance, while significantly reducing raw material costs. It has broad application prospects in the field of internal welding of batteries.
Claims
1. A method for preparing a lead-tin-titanium-tellurium-gallium alloy solder electrode, characterized in that, The specific steps are as follows: S1. The sponge titanium and the first part of tin are loaded into the furnace in a titanium-tin-titanium sandwich manner and heated and melted under vacuum conditions. After melting, the mixture is cast, vacuum cooled and crushed to obtain titanium-tin intermediate alloy particles. S2. The second part of tin, gallium, and tellurium are heated and melted under a protective atmosphere, cooled, and crushed to obtain tin-gallium-tellurium master alloy particles; S3. After heating and melting the lead ingot, add the titanium-tin intermediate alloy particles obtained in S1 and the tin-gallium-tellurium master alloy particles obtained in S2 in sequence. Cover the surface of the smelting system with a protective layer, stir until completely melted and mixed evenly, and cool down to 400-450℃ to obtain lead-tin-titanium-tellurium-gallium alloy liquid. S4. Inject the lead-tin-titanium-tellurium-gallium alloy liquid obtained in S3 into the pre-made solder forming mold, cool to room temperature, demold, and obtain lead-tin-titanium-tellurium-gallium alloy solder bar. The first portion of tin and the second portion of tin together constitute the total amount of tin in the lead-tin-titanium-tellurium-gallium alloy.
2. The method for preparing a lead-tin-titanium-tellurium-gallium alloy solder electrode according to claim 1, characterized in that, The lead-tin-titanium-tellurium-gallium alloy solder bar is smelted from the following components by weight percentage: titanium 0.005-0.1%, tellurium 0.05-0.2%, gallium 0.01-0.15%, tin 1.0-2.0%, with the balance being lead and unavoidable impurities.
3. The method for preparing a lead-tin-titanium-tellurium-gallium alloy solder electrode according to claim 2, characterized in that, In S1, the weight ratio of sponge titanium to the first part of tin is 1:5 to 10.
4. The method for preparing a lead-tin-titanium-tellurium-gallium alloy solder electrode according to claim 1, characterized in that, In S1, the vacuum degree under vacuum conditions is less than 1.0 Pa, the heating and melting temperature is 1350~1550℃, and the melting and holding time is 35~55 minutes.
5. The method for preparing a lead-tin-titanium-tellurium-gallium alloy solder electrode according to claim 3, characterized in that, In S2, the second part, consisting of tin, gallium, and tellurium, is melted in a vacuum quartz ampoule or a high-purity graphite crucible.
6. The method for preparing a lead-tin-titanium-tellurium-gallium alloy solder electrode according to claim 3, characterized in that, In S2, the second part of tin is the remaining tin after subtracting the first part of tin in S1 from the total weight of tin in the lead-tin-titanium-tellurium-gallium alloy; the protective atmosphere is a vacuum or an inert atmosphere.
7. The method for preparing a lead-tin-titanium-tellurium-gallium alloy solder electrode according to claim 1, characterized in that, In S2, the melting temperature is 600–750℃, and the melting holding time is 2–4 hours.
8. The method for preparing a lead-tin-titanium-tellurium-gallium alloy solder electrode according to claim 1, characterized in that, In S3, the lead ingot is heated to 600-700℃ after melting; the protective layer is borax or charcoal powder; after the alloy particles are completely melted, they are continuously stirred for 20-60 minutes.
9. A lead-tin-titanium-tellurium-gallium alloy solder bar, characterized in that, It is prepared by the preparation method according to any one of claims 1-8.
10. The application of the lead-tin-titanium-tellurium-gallium alloy solder electrode prepared by the preparation method according to any one of claims 1-8 in the internal welding of a storage battery, characterized in that, The solder strip is used for series and parallel welding of the battery plates' tabs, terminals, and bridge structures.
Citation Information
Patent Citations
Solder alloy and preparation method and application thereof
CN116275684A
